Teachers' Response to the Leadership Style of the Head of Madrasah Tsanawiyah Muhammadiyah Sulit Air - Ernadiati Ernadiati; Suswati Hendriani; Fathur Rahmi (al-fikrah: Jurnal Manajemen Pendidikan, 2021)
The leadership style of a principal certainly affects the progress of the school, including graduates, teacher performance and so on. The purpose of this study was to find out what leadership style is used by the principal at MTsM Sulit Air through teacher responses. The research method used is qualitative research with descriptive methods. Data collection techniques were conducted using interview, observation and documentation studies. The research subjects were teachers at MTsM Sulit Air. The leadership style of the head of MTsM Sulit Air that stands out is a transformative and democratic leadership style. This can be seen from the results of the study which can be concluded that the principal is responsible in every task, is ready to accept the risks of what he does, accepts criticism, consults when there are problems and many other principals' attitudes that support the principal's transformative leadership style and also democratic.